Death switch for gene therapy: application to erythropoietin transgene expression - Souza,D.S. (2010)
The effectiveness of the caspase-9-based artificial "death switch" as a safety measure for gene therapy based on the erythropoietin (Epo) hormone was tested in vitro and in vivo using the chemical inducer of dimerization, AP20187. Plasmids encoding the dimeric murine Epo, the tetracycline-controlled transactivator and inducible caspase 9 (ptet-mEpoD, ptet-tTAk and pSH1/Sn-E-Fv’-Fvls-casp9-E, respectively) were used in this study. AP20187 induced apoptosis of iCasp9-modified C2C12 myoblasts. In vivo, two groups of male C57BI/6 mice, 8-12 weeks old, were injected intramuscularly with 5 µg/50 g ptet-mEpoD and 0.5 µg/50 g ptet-tTAk. There were 20 animals in group 1 and 36 animals in group 2. Animals from group 2 were also injected with the 6 µg/50 g iCasp9 plasmid. Seventy percent of the animals showed an increase in hematocrit of more than 65% for more than 15 weeks. AP20187 administration significantly reduced hematocrit and plasma Epo levels in 30% of the animals belonging to group 2. TUNEL-positive cells were detected in the muscle of at least 50% of the animals treated with AP20187. Doxycycline administration was efficient in controlling Epo secretion in both groups. We conclude that inducible caspase 9 did not interfere with gene transfer, gene expression or tetracycline control and may be used as a safety mechanism for gene therapy. However, more studies are necessary to improve the efficacy of this technique, for example, the use of lentivirus vector.